Advancing Research on the Complex Interrelations Between Atrial Fibrillation and Heart Failure: A Report From a US National Heart, Lung, and Blood Institute Virtual Workshop. Issue 23 (9th June 2020) - Al-Khatib, Sana M.; Benjamin, Emelia J.; Albert, Christine M.; Alonso, Alvaro; Chauhan, Cynthia; Chen, Peng-Sheng; Curtis, Anne B.; Desvigne-Nickens, Patrice; Ho, Jennifer E.; Lam, Carolyn S.P.; Link, Mark S.; Patton, Kristen K.; et al.
Abstract : The interrelationships between atrial fibrillation (AF) and heart failure (HF) are complex and poorly understood, yet the number of patients with AF and HF continues to increase worldwide. Thus, there is a need for initiatives that prioritize research on the intersection between AF and HF. This article summarizes the proceedings of a virtual workshop convened by the US National Heart, Lung, and Blood Institute to identify important research opportunities in AF and HF. Key knowledge gaps were reviewed and research priorities were proposed for characterizing the pathophysiological overlap and deleterious interactions between AF and HF; preventing HF in people with AF; preventing AF in individuals with HF; and addressing symptom burden and health status outcomes in AF and HF. These research priorities will hopefully help inform, encourage, and stimulate innovative, cost-efficient, and transformative studies to enhance the outcomes of patients with AF and HF.